Evaluating Hybrid Citizen-AI Legal Monitoring Systems for Strengthening Public Oversight in Urban Environmental Governance - Rezki Akbar Norrahman; Aan Puji Kistanto; Aya Hamdi Ramadan (International Forum of Researchers and Lecturers, 2024)
This study evaluates the effectiveness of a hybrid citizen–AI legal monitoring system in enhancing urban environmental governance. The hybrid system integrates citizen-driven reporting platforms with AI-powered legal monitoring tools to address the challenges of weak public oversight in urban environmental management. By implementing the system in three metropolitan areas, the study explores how real-time data collection through citizen reports, combined with AI-driven analysis, can improve the accuracy, speed, and responsiveness of identifying environmental violations. The results showed a 45% improvement in oversight effectiveness, demonstrating the potential of hybrid systems to enhance monitoring capabilities beyond traditional methods. The AI system, capable of analyzing large datasets and providing timely insights, enabled quicker identification and categorization of violations such as pollution and waste management issues. The integration of citizen involvement through digital platforms allowed for more inclusive data collection, enhancing the quality and volume of information available for decision-making. This synergy between human participation and AI-driven analysis improved the speed of response to urban environmental challenges, making the system more adaptive and efficient. However, challenges such as data reliability and variable citizen participation rates were identified, suggesting the need for strategies to encourage consistent engagement and ensure the accuracy of reported data. The study concludes that hybrid citizen–AI systems can significantly improve urban governance by enhancing transparency, accountability, and responsiveness, offering a promising solution for cities seeking to address environmental issues more effectively.